Cerenkov Luminescence Tomography for Small Animal Imaging - Li, Changqing (2010)
Cerenkov radiation is a well-known phenomenon, in which optical photons are emitted by charged particles moving faster than the speed of light in a medium. We have observed Cerenkov photons emitted from beta-emitting radiotracers such as (18)F-fluorodeoxyglucose using a sensitive CCD camera. Phantom and in vivo mouse imaging experiments have demonstrated that surface measurements of the emitted Cerenkov optical photons could be used to reconstruct the radiotracer activity distribution inside an object by modeling the optical photon propagation with the diffusion equation and reconstructing the optical emission source distribution iteratively with a preconditioned conjugate gradient method (PCG). This is analogous to methods used for bioluminescence tomography. We refer to this as Cerenkov luminescence tomography (CLT), allowing the biodistribution of diagnostic and therapeutic beta-emitting radiolabeled agents to be imaged by detection and reconstruction of the optical Cerenkov signal.